Ever since Darwin : reflections in natural history - Gould, Stephen Jay (United States of America : Norton Paperback, 1979)
Stephen Jay Grould is one of the brillant of our younger biologists, gifted, among other things, whit the ability to write. These essays, on a fascinating variety of topics in natural history, are original, informative, enlightening, and stimulating.
Contents Prologue 11 1. DARWIANA 2. HUMAN EVOLUTION 3. ODD ORGANISMS AND EVOLUTIONARY EXEMPLARS 4. PATTERNS AND PUNCTUATIONS IN THE HISTORY OF LIFE 5. THEORIES OF THE EARTH 6. SIZE AND SHAPE, FROM CHURCHES TO BRAINS TO PLANTETS 7. SCIENCE IN SOCIETY - A HISTORICAL VIEW 8. THE SCIENCE AND POLITICS OF HUMAN NATURE Epilogue Bibliography Index
Incluye Contents
Incluye Prologue
Keywords: ENGLISH LITERATURE; NATURAL HISTORY; STORY